2018
DOI: 10.1038/s41556-017-0027-6
|View full text |Cite
|
Sign up to set email alerts
|

Tumour spheres with inverted polarity drive the formation of peritoneal metastases in patients with hypermethylated colorectal carcinomas

Abstract: Metastases account for 90% of cancer-related deaths; thus, it is vital to understand the biology of tumour dissemination. Here, we collected and monitored >50 patient specimens ex vivo to investigate the cell biology of colorectal cancer (CRC) metastatic spread to the peritoneum. This reveals an unpredicted mode of dissemination. Large clusters of cancer epithelial cells displaying a robust outward apical pole, which we termed tumour spheres with inverted polarity (TSIPs), were observed throughout the process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
106
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 101 publications
(113 citation statements)
references
References 57 publications
6
106
1
Order By: Relevance
“…Four days after recovery, we performed time‐lapse imaging during 48 h and stained for actin and ezrin at end point. CRC histotype assessment indicated that 2 out of 10 patients had mucinous CRC, correlating with the inverted apico‐basolateral polarity of the explants we observed ex vivo and consistent with our previous study (Zajac et al , ) (Figs EV2A and EV2B, patients #E and #H, excluded from the present study focusing on NOS adenocarcinomas). For all patients with adenocarcinoma (8/8), all tumour explants remained cohesive and most displayed one or multiple lumens (77.7 ± 6.3% and 81.6 ± 4.9% visualized by DIC or ezrin staining, respectively, Figs A and B, EV2C and D).…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Four days after recovery, we performed time‐lapse imaging during 48 h and stained for actin and ezrin at end point. CRC histotype assessment indicated that 2 out of 10 patients had mucinous CRC, correlating with the inverted apico‐basolateral polarity of the explants we observed ex vivo and consistent with our previous study (Zajac et al , ) (Figs EV2A and EV2B, patients #E and #H, excluded from the present study focusing on NOS adenocarcinomas). For all patients with adenocarcinoma (8/8), all tumour explants remained cohesive and most displayed one or multiple lumens (77.7 ± 6.3% and 81.6 ± 4.9% visualized by DIC or ezrin staining, respectively, Figs A and B, EV2C and D).…”
Section: Resultssupporting
confidence: 92%
“…We found that inhibition of ROCK triggers the formation of leaders and the transition from non‐invasive to protrusive cohorts that undergo collective invasion. This is in contradiction with the pro‐invasive role of ROCK identified in CIMP CRCs explants (Zajac et al , ), mice xenografted with cell lines (Itoh et al , ; Croft et al , ; Sadok et al , ) or transgenic models of pancreatic cancer (Rath et al , ). However, our results are in agreement with the recent large‐scale in vivo RNAi screen revealing that loss of Myosin‐II triggers the formation of invasive skin cancers (Schramek et al , ) and that expression of active ROCK2 increases proliferation, but not invasion in similar models (Samuel et al , ).…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations